Enhancing urban governance through public private partnership : a study of solid waste management in Dhaka City - Begum, Asma Ara (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.